2020
DOI: 10.1029/2020jc016199
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Canary Current Diagnosed by Inverse Box Models

Abstract: Four hydrographic cruises carried out between ~26.5 and 31°N in the eastern North Atlantic Subtropical Gyre in fall (2016 and 2017) and spring (2017 and 2018) are used to identify water masses and infer oceanic circulation. Geostrophic velocities are initially adjusted by referencing them to data from a Lower Acoustic Doppler Current Profiler (LADCP) and later to velocities estimated with an inverse box model. The distribution of the intermediate water masses (700 to 1,400 m depth) varies seasonally. Antarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 43 publications
6
22
0
Order By: Relevance
“…Western boundary density anomalies were thus chosen as the independent variables representing each layer, with the exception of AAIW. The seasonal cycle of the AMOC is driven largely by seasonality at the eastern boundary (Chidichimo et al, 2010;Pérez-Hernández et al, 2015). The annual maximum northward transport at the eastern boundary and the AMOC occur around October (Vélez-Belchí et al, 2017) and is driven by changes in the circulation of the Canary Current (Casanova-Masjoan et al, 2020;Hernández-Guerra et al, 2017) and at intermediate depths (700-1400 dbar) by seasonal changes in the Intermediate Poleward Undercurrent (Hernández-Guerra et al, 2017;Vélez-Belchí et al, 2017).…”
Section: Developing the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Western boundary density anomalies were thus chosen as the independent variables representing each layer, with the exception of AAIW. The seasonal cycle of the AMOC is driven largely by seasonality at the eastern boundary (Chidichimo et al, 2010;Pérez-Hernández et al, 2015). The annual maximum northward transport at the eastern boundary and the AMOC occur around October (Vélez-Belchí et al, 2017) and is driven by changes in the circulation of the Canary Current (Casanova-Masjoan et al, 2020;Hernández-Guerra et al, 2017) and at intermediate depths (700-1400 dbar) by seasonal changes in the Intermediate Poleward Undercurrent (Hernández-Guerra et al, 2017;Vélez-Belchí et al, 2017).…”
Section: Developing the Modelmentioning
confidence: 99%
“…The annual maximum northward transport at the eastern boundary and the AMOC occur around October (Vélez-Belchí et al, 2017) and is driven by changes in the circulation of the Canary Current (Casanova-Masjoan et al, 2020;Hernández-Guerra et al, 2017) and at intermediate depths (700-1400 dbar) by seasonal changes in the Intermediate Poleward Undercurrent (Hernández-Guerra et al, 2017;Vélez-Belchí et al, 2017). Eastern boundary density anomalies have maximum subsurface variability around 1000 dbar (Chidichimo et al, 2010), so the AAIW layer was represented by an eastern boundary density anomaly between 800 and 1100 dbar. The multiple linear regression Eq.…”
Section: Developing the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal cycle of the AMOC is driven largely by seasonality at the eastern boundary (Chidichimo et al, 2010;Pérez-Hernández et al, 2015). The annual maximum northwards transport at the eastern boundary and the AMOC occur around October , and is driven by changes in the circulation of the Canary Current (Casanova-Masjoan et al, 2020;, and at intermediate depths ( 700-1400 dbar) by seasonal changes in the Intermediate Poleward Undercurrent . Eastern boundary density anomalies have maximum sub-surface variability around 1000 dbar (Chidichimo et al, 2010), so the AAIW layer was represented by an eastern boundary density anomaly between 800 and 1100 dbar.…”
Section: Interactive Commentmentioning
confidence: 99%
“…, several papers have appeared dealing with the seasonal cycle of the AMOC and the eastern boundary of the NASG. Pérez-Hernández et al(2015), Vélez-Belchí et al(2017), Hernández-Guerra et al(2017)andCasanova-Masjoan et al (2020), among others, have found a seasonal behaviour of the Canary Current in the Lanzarote Passage that explains the seasonal cycle of the AMOC. I think these papers deserve at least a brief comment in the manuscript.…”
mentioning
confidence: 96%